PENINGKATKAN HASIL BELAJAR SISWA MELALUI PENERAPAN PEMBELAJARAN AKTIF DENGAN STRATEGI KELOMPOK BELAJAR PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 3 LAMONGAN - Anin Dwi Susianti, (Pendidikan Ekonomi, 2009)
The research is intended to find out the implementation of active learning with group study strategies. This classroom action research consisted of three cycles, each of which included four stages. The data collection techniques were observationand testsin each cycle. The data were analyzed in descriptive qualitative manner by calcualting the average scores of the students learning results. The finding showed that the classical learning results in cycle 1 is 43.24 %, in cycle 2 is 83.78%, and in cycle 3 is 94.59 %. It means that active learning with group study strategies can be used in other lesson materials.